2010
DOI: 10.1016/j.juro.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Nephroureterectomy Versus Endoscopic Management for Upper Tract Urothelial Carcinoma

Abstract: When technically feasible and in select patients, endoscopic management provides cancer related and overall survival equivalent to that of nephroureterectomy in patients with low grade upper tract urothelial carcinoma at the cost of frequent re-treatments in many patients. Nephroureterectomy is standard treatment for high grade cancer when there is a normal contralateral kidney but endoscopy should be considered when there are imperative indications for nephron sparing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 18 publications
3
84
0
4
Order By: Relevance
“…Among 34 renal units managed endoscopically for low-grade UC of the UUT, cancer-specific and metastasis-free 5-year survival rates were 100% and 94%, respectively. However, 84% of patients had at least one ipsilateral recurrence [25]. A comparative review of outcomes in 131 patients with UC of the UUT demonstrated a recurrence risk three times as high for NSS than for RNU.…”
Section: Discussionmentioning
confidence: 99%
“…Among 34 renal units managed endoscopically for low-grade UC of the UUT, cancer-specific and metastasis-free 5-year survival rates were 100% and 94%, respectively. However, 84% of patients had at least one ipsilateral recurrence [25]. A comparative review of outcomes in 131 patients with UC of the UUT demonstrated a recurrence risk three times as high for NSS than for RNU.…”
Section: Discussionmentioning
confidence: 99%
“…Due to modern day advances and earlier diagnosis of lower stage tumors, laparoscopic surgery has supplanted traditional open surgical techniques, and endoscopic or segmental surgical options have taken on a greater role in management. More conservative, less invasive approaches in the management of UTUC have shown promise due to their improved perioperative morbidity, cosmesis, and earlier convalescence [14]. Despite these advantages, the efficacy and oncological safety of these laparoscopic and endoscopic procedures is a source of concern with the lack of long-term follow-up data available [15].…”
Section: Historical Perspectivementioning
confidence: 99%
“…There exists a significant risk of under staging and undertreatment in conservatively managed upper urinary tract tumors [14]. In addition to the need for improved diagnostic modalities, further investigation into treatment options must be performed.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Hence, we selected the one with more areas and patients. After rounds of screening, twenty-three studies including 1587 KS and 3996 NU patients were enrolled meta-analysis at last (Hall et al, 1998;Shiraishi et al, 2003;Chen et al, 2005;Roupret et al, 2006;Giannarini et al, 2007;Lehmann et al, 2007;Lucas et al, 2008;Dragicevic et al, 2009;Gadzinski et al, 2010;Jeldres et al, 2010;Raymundo et al, 2011;Bin et al, 2012;Bing-bing et al, 2012;Colin et al, 2012;Grasso et al, 2012;Bagrodia et al, 2013;Cutress et al, 2013;Fajkovic et al, 2013;Klatte et al, 2013;Dalpiaz et al, 2014;Fukushima et al, 2014;Hoffman et al, 2014;Hung et al, 2014). All included studies were retrospective comparative study; no randomized controlled trials were identified.…”
Section: Literature Filtration and Quality Assessmentmentioning
confidence: 99%
“…Renal function preservation is becoming recognized and kidney-sparing procedures are reserved for selected patients with lowgrade UTUC in EAU guidelines . Kidney-sparing management (KS) has been reported with durable prognostic outcomes as nephroureterectomy in several studies (Gadzinski et al, 2010;Jeldres et al, 2010;Cutress et al, 2013;Fukushima et al, 2014). Kidney preservation treatments mainly comprise segmental ureterectomy and endoscopic resection or ablation.…”
Section: Introductionmentioning
confidence: 99%